Long-term follow-up for Psychological stRess in Intensive CarE (PRICE) survivors: study protocol for a multicentre, prospective observational cohort study in Australian intensive care units. Issue 1 (25th January 2019) - Rai, Sumeet; Brown, Rhonda; van Haren, Frank; Neeman, Teresa; Rajamani, Arvind; Sundararajan, Krishnaswamy; Mitchell, Imogen
Abstract : Introduction: There are little published data on the long-term psychological outcomes in intensive care unit (ICU) survivors and their family members in Australian ICUs. In addition, there is scant literature evaluating the effects of psychological morbidity in intensive care survivors on their family members. The aims of this study are to describe and compare the long-term psychological outcomes of intubated and non-intubated ICU survivors and their family members in an Australian ICU setting. Methods and analysis: This will be a prospective observational cohort study across four ICUs in Australia. The study aims to recruit 150 (75 intubated and 75 non-intubated) adult ICU survivors and 150 family members of the survivors from 2015 to 2018. Long-term psychological outcomes and effects on health-related quality of life (HRQoL) will be evaluated at 3 and 12 months follow-up using validated and published screening tools. The primary objective is to compare the prevalence of affective symptoms in intubated and non-intubated survivors of intensive care and their families and its effects on HRQoL. The secondary objective is to explore dyadic relations of psychological outcomes in patients and their family members. Ethics and dissemination: The study has been approved by the relevant human research ethics committees (HREC) of Australian Capital Territory (ACT) Health (ETH.11.14.315), New South Wales (HREC/16/HNE/64), South Australia (HREC/15/RAH/346). The results of this study will be published in a peer-reviewed medical journal and presented to the local intensive care community and other stakeholders. Trial registration number: ACTRN12615000880549; Pre-results.